Dopamine guides competition for cognitive control: Common effects of haloperidol on working memory and response conflict. (April 2019) - Fallon, Sean James; Muhammed, Kinan; Drew, Daniel S.; Ang, Yuen-Siang; Manohar, Sanjay G.; Husain, Masud
Abstract: Several lines of evidence suggest that dopamine modulates working memory (the ability to faithfully maintain and efficiently manipulate information over time) but its specific role has not been fully defined. Nor is it clear whether any effects of dopamine are specific to memory processes or whether they reflect more general cognitive mechanisms that extend beyond the working memory domain. Here, we examine the effect of haloperidol, principally a dopamine D2 receptor antagonist, on the ability of humans to ignore distracting information or update working memory contents. We compare these effects to performance on an independent measure of cognitive control (response conflict) which has minimal memory requirements. Haloperidol did not selectively affect the ability to ignore or update, but instead reduced the overall quality of recall. In addition, it impaired the ability to overcome response conflict. The deleterious effect of haloperidol on response conflict was selectively associated with the negative effect of the drug on ignoring – but not updating – suggesting that dopamine affects protection of working memory contents and inhibition in response conflict through a common mechanism. These findings provide new insights into the role of dopamine D2 receptors on human cognition. They suggest that D2 receptor effects on protecting the memory contents from distraction might be related to a more general process that supports inhibitory control in contexts that do not require working memory.